Usage, knowledge and attitudes towards electronic cigarettes use among nursing students in Croatia: a cross-sectional study - Leopold Kajan; Livia Puljak; Ivica Matić; Mario Marendić; Sanja Zoranić; Kata Ivanišević; Dijana Majstorović; Zrinka Puharić; Nataša Skitarelić; Marijana Neuberg; Ivana Barać; Snježana Čukljek; et al. (BMC Nursing)
Abstract Background Evidence shows harmful effects of e-cigarettes on health. There is limited data on the use of e-cigarettes among nursing students. This study aimed to investigate the usage, knowledge, and attitudes towards e-cigarettes among nursing students in Croatia, as well as their views on the role of nurses in counseling patients and assisting with smoking cessation. Methods This cross-sectional study was conducted via an online questionnaire among nursing students at 10 universities in Croatia in March/April 2024. Students were asked questions about socio-demographics, knowledge and attitudes towards e-cigarettes and their views on the role of nurses in counseling patients and assisting with smoking cessation. Results The study included 1,039 participants; 89% were women, 43% were smokers; 53% used e-cigarettes and 76% used them for recreational purposes. 21% of participants agreed that e-cigarettes are an effective method for quitting smoking. More than half indicated that e-cigarettes could encourage non-smokers to start smoking. The majority (60%) reported that they had never received education on smoking cessation at university. Furthermore, 66% stated that they did not feel confident advising smokers about e-cigarettes. The majority (70%) considered physicians to be the most knowledgeable health experts to advise and educate users of e-cigarettes. There were no significant differences in attitudes between smokers and non-smokers on the use of e-cigarettes. Participants demonstrated insufficient knowledge about e-cigarettes. Non-smokers had more positive attitudes towards the role of nurses in combating smoking compared to smokers. Participants who had received education on smoking cessation were more willing to advise smokers and had clearer views on the risks and the importance of the nurse’s role in the quitting process compared to those who had not received such education. Smoking status and age were significant predictors of counseling confidence. Conclusion The study found a high prevalence of smoking and e-cigarette use among Croatian nursing students, along with limited knowledge and generally negative attitudes towards e-cigarettes. It highlighted gaps in education regarding the health risks of e-cigarettes and the lack of practical skills needed to help smokers quit, suggesting that nursing programs should update their curricula to better prepare students in these areas.